Investigation of isophorone diisocyanate microcapsules to improve self-healing properties and sulfate resistance of concrete. (20th September 2021) - Du, Wei; Lin, Runsheng; Liu, Quantao
Highlights: Microcapsules with isophorone diisocyanate as the healing agent were prepared. The microcapsule shells were made of paraffin wax, polyethylene wax, & nano silica. The impact of the microcapsule on various concrete properties was investigated. The sulfate resistance & self-healing properties of concrete were greatly improved. Abstract: Sulfate attack causes internal cracking of concrete and affects the durability of concrete structures. The durability of concrete under sulfate attack is crucial to structural safety and serviceability. Microcapsules can self-heal microcracks in concrete and improve its durability. Microcapsules with isophorone diisocyanate (IPDI) as the healing agent and paraffin wax, polyethylene wax, and nano silica as shells were prepared to improve the sulfate resistance and self-healing properties of concrete. The mass loss, mechanical properties, impermeability, and pore size distribution of the concrete after sulfate dry-wet cycles were determined. Ultrasonic testing was used to evaluate concrete sulfate resistance and self-healing properties, as a prominent nondestructive testing technique. The results showed that the addition of microcapsules significantly improved the sulfate resistance and self-healing properties. Concrete containing nano silica/paraffin wax/polyethylene wax encapsulated IPDI microcapsules exhibited good sulfate resistance and self-healing properties. Scanning electron microscopy revealed that concrete containing microcapsules exposed to sulfate attack produced healing products with a mesh-like structure in the pores after a 14-d self-healing. These healing products can improve microstructure and self-healing properties.